PENGARUH LATIHAN DRIBBLING SHIELDING FUNDAMENTAL TERHADAP KOORDINASI DRIBBLE PADA KLUB SEPAKBOLA (SSB) CHEVRON RUMBAI U-12 - Suherman, Muhammad Iqbal Suherman Iqbal; Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, This research want to know is there any effect of dribbling shielding fundamental  exercise toward dribbling coordination of U-12 Chevron Rumbai Pekanbaru football club, so when doing dribbling, the opposing player will hardly grab the ball to increase the chances in scoring and getting win. This research was experimental research. The population in this research was the athletes of Chevron Rumbai Pekanbaru football club, while the sample was the 12-year-old athletes of the football club in the total of 16. Sampling technique used in this research was Total Sampling. According to Arikunto (2006: 134), if the population are less of 100 people, it is better to take all. Instrument that was used in this research was soccer driblle test, which is aimed to measure the ankle coordination while dribbling. The data was analyzed by using statistic to examine the normality with liliefors test on the significant level 0,05α. The submitted hypothesis was there is a significant effect of dribbling shielding fundamental toward coordination. Based on the data analysis, t-test showed T hitung was 5.02 dan T table was 1,753. It means that T hitung > T table. Based on the statistic data analysis, the average of pretest was 18.57 and the average of posttest was 17.08. It shows that the data was normal. In conclusion, there was a significant effect of dribbling shielding fundamental exercise toward coordination of U-12 Chevron Rumbai Pekanbaru football club. Keywords : Dribbling Shielding Fundamental, Coordination